2021
DOI: 10.1038/s41598-021-81735-1
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of E-cadherin in pluripotent stem cells triggers partial EMT

Abstract: Epithelial to mesenchymal transition (EMT) is a critical cellular process that has been well characterized during embryonic development and cancer metastasis and it also is implicated in several physiological and pathological events including embryonic stem cell differentiation. During early stages of differentiation, human embryonic stem cells pass through EMT where deeper morphological, molecular and biochemical changes occur. Though initially considered as a decision between two states, EMT process is now r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 32 publications
(38 reference statements)
2
25
0
Order By: Relevance
“…Metastasis is one of the key molecular steps affecting the prognosis of advanced GC patients. And Epithelial-mesenchymal transition (EMT) is one of the important steps in the process related to metastasis in gastric cancer ( Valastyan and Weinberg, 2011 ).EMT refers to the phenomenon that epithelial cells transform into mesenchymal cells under specific physiological and pathological condition ( Aban et al, 2021 ). And it can down-regulate the epithelial markers E-cadherin, ZO-1, etc., which can inhibite the characteristics and behavior of epithelial cells.…”
Section: E-cadherinmentioning
confidence: 99%
See 1 more Smart Citation
“…Metastasis is one of the key molecular steps affecting the prognosis of advanced GC patients. And Epithelial-mesenchymal transition (EMT) is one of the important steps in the process related to metastasis in gastric cancer ( Valastyan and Weinberg, 2011 ).EMT refers to the phenomenon that epithelial cells transform into mesenchymal cells under specific physiological and pathological condition ( Aban et al, 2021 ). And it can down-regulate the epithelial markers E-cadherin, ZO-1, etc., which can inhibite the characteristics and behavior of epithelial cells.…”
Section: E-cadherinmentioning
confidence: 99%
“…The decrease of E-cadherin expression on the cell membrane leads to weakening or disappearance of the interaction between cells and inhibit the activation of transcription factors (Snail, Slug, Twist and ZEB-1), resulting in EMT ( Kalluri and Weinberg, 2009 ; Aban et al, 2021 ). Studies have found that Snail family transcription factors are strong repressors of E-cadherin gene transcription.…”
Section: E-cadherinmentioning
confidence: 99%
“…Moreover, to move to the correct position to conduct sub-population differentiation, the progenitor cells can modulate the E-cadherin to upregulate SNAIL1/2 resulting in partial EMT [ 214 ]. The expression of SNAIL1 can serve as an EMT hallmark in cell biology, especially in cancer progression.…”
Section: Defined Emt Molecules In Cancermentioning
confidence: 99%
“…Even though downregulation of E-cadherin has been shown to induce EMT independently in some cancer models ( 16 , 17 ), a study carried out by Vafaizadeh and her colleagues ( 18 ) suggests that active β-catenin is essential for invasion in culture and experimental metastasis model attributed in part to detachment of adherens junctions during early EMT and subsequent degradation. Deducing in tandem with their structural arrangement, the implication of these findings is that β-catenin acts cooperatively with E-cadherin to initiate EMT ( Figure 2 ), suggesting that β-catenin may be an important therapeutic target in certain types of cancer.…”
Section: Emt and Metastasismentioning
confidence: 99%